Three‐dimensional, impulsive magnetic reconnection in a laboratory plasma. Issue 2 (22nd January 2013) - Dorfman, S.; Ji, H.; Yamada, M.; Yoo, J.; Lawrence, E.; Myers, C.; Tharp, T. D.
<x xml:space="preserve">Abstract</x> [1] Impulsive, local, 3‐D reconnection is identified for the first time in a laboratory current sheet. The events observed in the Magnetic Reconnection Experiment are characterized by large local gradients in the third direction and cannot be explained by 2‐D models. Detailed measurements show that the ejection of flux rope structures from the current sheet plays a key role in these events. By contrast, even though electromagnetic fluctuations in the lower hybrid frequency range are also observed concurrently with the impulsive behavior, they are not the key physics responsible. A qualitative, 3‐D, two‐fluid model is proposed to explain the observations. The experimental results may be particularly applicable to space and astrophysical plasmas where impulsive reconnection occurs.